Mindanao, Konflik dan Terorisme: Kajian Pendahuluan atas Ketegangan di Filipina Selatan - Al Chaidar; M. Akmal; Saifullah Ali; Nanda Amalia; Dara Quthni Effida (SIASAT, 2018)
Mindanao is the second largest island in Philippines and one of the three main island groups along with Luzon and Visayas, the South Philippines . Mindanao is one of region in Southeast Asia which has been spectacularly a bright spot of world-class terrorism, because of the very high incidents of piracy and the ever-growing threat of terrorism. Southeast Asia is the region most vulnerable to piracy, accounting for about 50 percent of all attacks worldwide. This situation is exacerbated by the indigenous people of terrorist groups with strong maritime traditions. The nexus exchange between piracy and terrorism makes maritime terrorism in Southeast Asia a regional security concern. The Abu Sayyaf (ASG), Free Aceh Movement (Gerakan Aceh Merdeka, GAM), and Jemaah Islamiyah (JI) are the three terrorist groups in South Philippines, Southeast Asia with the intent and proven ability to engage in maritime terrorism. Of this group, the Abu Sayyaf is the best known but least understood and it has been source of tension in the South Philippines and Southeast Asia